1
$\begingroup$

Simplify the following Boolean expression: $$F=A'B'C'+A'B'C+A'BC'+AB'C'+AB'C.$$

I have tried and am getting stuck at $A'+B'+C'+A'BC'$.

According to the K-Map it should get to $B'+A'C'$.

$\endgroup$
0
$\begingroup$

$F$ is NOT equal to $$A'+B'+C'+A'BC'=A'+B'+C'+A'BC'=A′+B′+C′(1+A′B)=A′+B′+C′.$$ If $A$ and $B$ are true and $C$ is false then $F$ is false whereas $A′+B′+C′$ is true.

In order to simplify the given Boolean expression, note that $A'B'C'=A'B'C'+A'B'C'$ and \begin{align*} F&=(A'B'C'+A'B'C+AB'C'+AB'C)+(A'BC'+A'B'C')\\ &=B'(A'(C'+C)+A(C'+C))+A'C'(B+B')\\ &=B'(A'+A)+A'C'=B'+A'C'\\ \end{align*} where we used the fact that $A+A'=B+B'=C+C'=1$.

$\endgroup$
  • $\begingroup$ I cant get how you get to the first step $\endgroup$ – Seffu Jul 11 '17 at 14:36
  • $\begingroup$ @Seffu Note that $A'B'C'=A'B'C'+A'B'C'$. Is it clear now? $\endgroup$ – Robert Z Jul 11 '17 at 14:37
  • $\begingroup$ is there a better editor for me o post the question as it is??? $\endgroup$ – Seffu Jul 11 '17 at 14:44
  • $\begingroup$ Hi Robert would there be any difference if some of the bars are continous??? $\endgroup$ – Seffu Jul 11 '17 at 15:11
  • $\begingroup$ F=A'+B'+C'+A'BC $\endgroup$ – Seffu Jul 12 '17 at 3:40
0
$\begingroup$

There is a handy equivalence rule called Adjacency:

Adjacency

$PQ + PQ' = P$

'Adjacency' is of course named after the fact that it reflects exactly what you do in a K-map: you group together adjacent cells in order to get a simpler expression.

Another very useful principle is called Reduction:

Reduction

$P + P'Q = P + Q$ (that is, in the context of $P$, the term $P'Q$ reduces to just $Q$)

Applied to your problem:

$$A'B'C'+A'B'C+A'BC'+AB'C'+AB'C= \text{ (Adjacency) }$$

$$A'B'+A'BC'+AB'= \text{ (Adjacency) }$$

$$B'+A'BC'\text{ (Reduction) }$$

$$B'+A'C'$$

If you didn't know these two equivalences yet ... put them in your toolbox immediately!

And here is one more:

Absorption

$P+PQ=P$

$P(P+Q)=P$

$\endgroup$
  • $\begingroup$ What will A'+B'+C'+A'BC' give me? $\endgroup$ – Seffu Jul 12 '17 at 3:39
  • $\begingroup$ @Seffu That will be A'+B'+C' by Absorption. That is, the A' term 'absorbs' the A'BC' term. I'll add Absorption to the post: you definitely need to know that one as well if you want to become skilled at Boolean algebra $\endgroup$ – Bram28 Jul 12 '17 at 11:17

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.